Pesantren Graduates As Mediators Of Personalised Strategies - AlQadrie, Syarif Ali; Edy Wahyudi; Ridha Nurhaliza (JIEMAN: Journal of Islamic Educational Management, 2024)
Alumni have an important role in the development of the boarding school, especially as a connector of information in the form of personal promotion, so the attachment of alumni and the boarding school must be maintained and maximally empowered. Alumni also become the mediators of the boarding school in promoting it to the community in accordance with the function of alumni in building a good image of the boarding school. This research focuses on 1) how the role of alumni as mediators and personal promotion strategies. 2) What is the boarding school's promotion strategy through alumni? This research uses descriptive qualitative research through data collection techniques based on the results of observations and interviews in the field related to the required data. The results of this study indicate that the role of alumni is very influential in conveying information at the boarding school, and the boarding school's strategy in carrying out promotions involves alumni as a conduit of information to the community regarding the boarding school. In addition, the strategy is carried out by providing reinforcement to alumni when going into the community to invite continuing education to the boarding school based on good manners. Alumni memiliki peranan penting dalam perkembangan pondok pesantren terutama menjadi penyambung informasi dalam bentuk promosi secara personal sehingga keterikatan alumni dan pondok pesantren harus dijaga dan diberdayakan secara maksimal. Alumni juga menjadi mediator pondok pesantren dalam mempromosikannya kepada masyarakat sesuai dengan fungsi alumni dalam membangun citra yang baik dari pondok pesantrennya. Penelitian ini fokus 1) bagaimana peran alumni sebagai mediator dan strategi promosi secara personal. 2) bagaimana strategi promosi pondok pesantren melalui alumni. Penelitian ini menggunakan jenis penelitian kualitatif secara deskriptif melalu teknik pengumpulan data berdasarkan hasil observasi dan wawancara dilapangan terkait data yang diperlukan. Hasil dari penelitian ini menunjukkan bahwa peran alumni sangat berpengaruh dalam menyampaikan informasi dipondok pesantren dan strategi pondok pesantren dalam melaksanakan promosi melibatkan alumni sebagai penyambung informasi kepada masyarakat terkait pondok pesantrennya.Selain itu strategi yang dilakukan dengan cara memberikan penguatan kepada alumni ketika terjun ke masyarakat untuk mengajak melanjutkan pendidikan ke pondok pesantren dengan berlandaskan akhlakul karimah.